The Vernacularization of the Qur’an in the Acehnese Language: Cultural Manifestations in the Work of Tgk. Mahjiddin Jusuf - Unzila, Alifia Rizqa (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and Objectives: This study examines the Acehnese poetic translation of the Qur’an by Tgk. Mahjiddin Jusuf as a form of vernacularization that integrates linguistic, cultural, and religious elements. Rather than merely conveying the literal meaning of the Qur’anic text, Jusuf’s Al-Qur’an Al-Karim dan Terjemahan Bebas Bersajak dalam Bahasa Aceh functions as a cultural interpretation rooted in local norms and values. Methods: Utilizing a qualitative method with thematic analysis, the research analyzes purposively selected verses that contain elements of Acehnese culture, including politeness strategies, customary practices, and indigenous vocabulary. Main Results: Findings reveal that the translation embodies Acehnese identity through distinct vocabulary choices, such as boh ara (figs) and sineuk pade (wheat), and the integration of communal customs like peumulia jamee (honoring guests) and khanduri (traditional feasts). These linguistic and cultural adaptations not only localize the Qur’anic message but also reflect the translator’s intent to make the sacred text contextually resonant and spiritually accessible to Acehnese readers. Contributions: By foregrounding a non-Arab perspective, this study contributes to the diversification of Qur’anic translation discourse and challenges the dominance of Arab-centric or Western interpretive frameworks. It emphasizes the importance of sociocultural translation, arguing that translating the Qur’an entails negotiating meaning within specific cultural matrices. Conclusions: Jusuf’s work exemplifies vernacularization as both a method of cultural tafsir and a medium of dakwah anchored in local tradition and religious understanding.